The complete mitochondrial genome of the lizard subspecies, Phrynocephalus vlangalii vlangalii (Reptilia, Squamata, Agamidae). Issue 1 (2nd January 2018) - Yang, Kun; Wo, Yubin; Zhou, Yulong; Jin, Yuanting
Abstract: The complete mitochondrial genome was sequenced from the toad-headed lizard, Phrynocephalus vlangalii vlangalii. The overall length of mitogenome is 16, 319 bp, including 22 tRNA, 13 protein coding genes, 2 rRNA genes, and 2 control regions. The gene order and content were same with the published congeneric mitogenomes, besides the small portion between tRNA-Pro and tRNA-Phe .